Problematika Persyaratan Sertifikat Vaksin pada Ruang Publik - Alfina, Rizka (Jurnal Riset dan Pengabdian Masyarakat, 2022)
To accelerate the handling of the spread of Covid-19 in Indonesia. Vaccination in Indonesia has begun to be marked by President Jokowi as the recipient of the first dose of vaccine, which after two weeks was followed by a second dose of vaccination. Proof as a person who has taken the Covid-19 vaccine is the receipt of the vaccination certificate. Ideally, the implementation of vaccination consists of providing adequate facilities and providing the widest possible vaccination for free, as well as opening access to vaccination services, for example through clinics that have not been used optimally. In this case, a more in-depth study is needed to determine the extent to which the obligation to show vaccination certificates in public spaces and the legal problems that arise are important. The vaccine certificate requirement policy will begin trials on August 10-16, 2021 in four cities, including: Jakarta, Bandung, Surabaya, and Semarang. The formulation of the problem in this research will focus on what the impact is felt by the community, what are the problems and regulations that explain the policies issued, regarding Indonesia, what actions are taken to implement vaccine certificates as a requirement for access to public spaces, which countries have implemented policies related to this and what is the view of Islamic law regarding this policy. The method used in this study uses a qualitative approach and also Robert N. Entman's framing analysis using the online media that the researchers chose in this study, KOMPAS.com, with news uploaded to the media's online news portal. The results obtained from this study indicate that the implementation of the policy on vaccine certificate requirements in the public sphere is considered to violate the principles of justice and discrimination. Judging from the uneven distribution of vaccines in various regions and the difficulty of access and reach of the Covid-19 vaccine.